Melanoma Disparities among US Hispanics: Use of the Social Ecological Model to Contextualize Reasons for Inequitable Outcomes and Frame a Research Agenda - Valerie M. Harvey; Charlene W. Oldfield; Jarvis T. Chen; Karl Eschbach (Journal of Skin Cancer)
Cutaneous melanoma is a significant public health concern, accounting for thousands of deaths annually in the US. Early detection and diagnosis are critical given the poor prognosis and limited treatment options of advanced-stage disease. While non-Hispanic whites have higher incidence rates of melanoma, Hispanics are typically diagnosed at later disease stages and suffer higher morbidity and mortality. Currently, there is a paucity of literature investigating the root causes underlying these trends among Hispanics. Given that Hispanics are the most rapidly expanding demographic segment in the US, it is essential for cancer control efforts to elucidate the major determinants of their poor melanoma outcomes. Herein, we use the social ecological model as a framework to explore the multitude of influences on melanoma disparities among Hispanics and provide recommendations for planning future studies and interventions.